Design of model predictive control (MPC) system for air inlets in an air-conditioned room - Ang, Zhen Jie (2017)
Modeling a heating, ventilating and air-conditioning (HVAC) system to promote energy effectiveness hence leads to low cost of energy and at the same time, maintaining or enhancing the thermal comfort for occupants. With the application of computational fluid dynamics (CFD), a software which is capable on identifying and enable to simulate the expecting flow path for both thermal and velocity within rooms and buildings. This advantage provides the engineers the ability to predict the condition within the room without conducting multiple experiments under required specification. The aim of this study is to obtain an ideal airflow and temperature distribution for an air conditioning room and building. This study uses Ansys FLUENT to simulate the ventilation in simple structures and analyses the airflow patterns within the room. Configurations are simulate with varying parameters, namely delivered air velocity, position of inlet(s) and angle of delivery within each room. Occupier and furniture are also included in some configurations to create a more realistic study. Temperature contours and airflow pattern from different configurations are acquired from the simulations for analyzing. The analyzing process will study on thermal comfort level based on varies parameter setting. From this study, we identify that the different inlet location and delivery angle of an air inlet will contribute effect to the thermal comfort. This study enhanced the understanding of the supplied air velocity and the position of inlet and presence of furniture and occupant. The findings of this study can be applied to real-life situations.